Synthesis, structure and properties of some 5-R-4-phenyl-1,2,4-triazole-3-thiol derivatives - A. S. Hotsulia (Zaporozhye State Medical University, 2019)
Pyrrole, 1,2,4-triazole and indole derivatives belong to the group of aza-heterocyclic compounds, which have been associated with significant advances in the development of new drugs. Combining these heterocycles in one molecule increases the likelihood of detecting among these compounds substances with a certain kind of biological activity. The aim of the work was to optimize the conditions of synthesis and study the properties of S-alkylderivatives of 5-R-4-phenyl-1,2,4-triazole-3-thiol containing pyrrole and indolpropane fragments in their structure. Materials and methods. Pyrrole and indole-3-butanoic acid were used as key starting reagents. 4-Phenyl-5-(pyrrol-2-yl)-1,2,4-triazole-3-thiol was obtained by acylation, hydrazinolysis, nucleophilic addition of phenylisothiocyanate followed by intramolecular heterocyclization. For the synthesis of 5-(3-(indol-3-yl)propyl)-4-phenyl-1,2,4-triazole-3-thiol, the reaction of the interaction of the potassium salt of indole-3-butanoic acid with bromethane was carried out to obtain the appropriate ester. Subsequent stages of chemical conversion included hydrazinolysis reactions, the addition of phenylisothiocyanate, and alkaline cyclization. The structure of the obtained compounds was confirmed by data of elemental analysis, 1H NMR spectroscopy and IR-spectrophotometry. The individuality of substances was established by using high performance liquid chromatography with diode-array and mass spectrometric detection. Results. S-alkylderivatives of 5-(3-(indol-3-yl)propyl)-4-phenyl-1,2,4-triazole-3-thiol and 4-phenyl-5-(pyrrol-2-yl)-1,2,4-triazole-3-thiol has been synthesized and their structure was established and studied physical properties. The synthesized compounds have been subjected to the in silico molecular docking study against the kinases of anaplastic lymphoma by using the 2XP2 ligand, lanosterol 14-α-demethylase by using the 3LD6 ligand, cyclooxygenase-2 by using the ligand which were downloaded from the protein data bank (PDB). Conclusions. Molecular docking has shown the ability of the synthesized compounds to influence the kinase activity of anaplastic lymphoma, cyclooxygenase-2 and lanosterol-14-α-demethylase.